Spectral Analysis of Proton-Irradiated Natural MoO3 Relevant for Technetium-99m Radionuclide Production - Imam Kambali; Rajiman Rajiman; Parwanto Parwanto; Marlina Marlina; Kardinah Kardinah; Nur Huda; Ferdi Dwi Listiawadi; Herta Astarina; Ratu Ralna Ismuha; Heranudin Heranudin; Hari Suryanto (Institute for Research and Community Services (LPPM) ITB, 2020)
Due to the declining number of available nuclear reactors capable of Tc-99m production and tight regulations related to uranium enrichment, cyclotron-based Tc-99m production has recently been suggested as a new method to help ease Tc-99m supply shortages. In this investigation, a solid natural MoO3 target was irradiated using 11-MeV proton beams at variable proton doses. The proton doses were varied by varying the irradiation time while keeping the proton beam current constant at 20 µA. At the end of the bombardment, the post-irradiated solid MoO3 targets were analyzed for their radioactive contents using a portable gamma-ray spectroscopy system. The analysis was also performed for the post-irradiated targets after dissolving the solid MoO3 in a 6M NaOH solution. The experimental results indicated that as much as 75.71% of Tc-99m radioactivity was directly generated via a 100Mo(p,2n)99mTc nuclear reaction, while the rest of the Tc-99m radioactivity was a result of a 98Mo(n,Î³)99Moâ†’99mTc nuclear reaction. Apart from Tc-99m and Mo-99 radionuclides, some other radionuclides such as N-13, Tc-96, and Nb-96 were also recorded following temporal observation of the NaOH-dissolved MoO3. These experimental results open up the possibility of direct production of Tc-99m using a proton-accelerating cyclotron.